2021
DOI: 10.3233/npm-200518
|View full text |Cite
|
Sign up to set email alerts
|

Association of hemoglobin and spontaneous closure of the ductus arteriosus during the transitional period in very low birth weight infants

Abstract: OBJECTIVES: To determine the association between plasma hemoglobin (HB) at three time-points (birth, postnatal days 0–3 and 0–10) and spontaneous closure of the ductus arteriosus (sDAC). STUDY DESIGN: A retrospective case-control study of preterm infants born (2013–2016) between 24 and 29 weeks of gestational age (GA) was conducted in a level three perinatal center in Switzerland. We collected hemoglobin at birth, between days 0–3 and 0–10 in two distinct groups: (i) patients treated for a PDA and (ii) patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
4
0
2
Order By: Relevance
“…No entanto, o efeito dos valores de HB e HCT no hsPDA não é totalmente conhecido. 2 , 3 Joye et al, 10 relataram um aumento na frequência de hsPDA na presença de anemia grave que requer transfusão pós-parto. No mesmo estudo, interpretou-se que um nível de HB mais alto e estável nos primeiros dez dias de vida pode afetar positivamente o fechamento esperado do CA.…”
Section: Discussionunclassified
See 4 more Smart Citations
“…No entanto, o efeito dos valores de HB e HCT no hsPDA não é totalmente conhecido. 2 , 3 Joye et al, 10 relataram um aumento na frequência de hsPDA na presença de anemia grave que requer transfusão pós-parto. No mesmo estudo, interpretou-se que um nível de HB mais alto e estável nos primeiros dez dias de vida pode afetar positivamente o fechamento esperado do CA.…”
Section: Discussionunclassified
“…However, the effect of HB and HCT values on hsPDA is not fully known. 2 , 3 Joye et al 10 reported an increase in the frequency of hsPDA in the presence of severe anemia requiring postpartum transfusion. In the same study, it was interpreted that a higher and more stable HB level in the first ten days of life may positively affect the expected closure of the DA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations